Penerapan Standar Akuntansi Keuangan No. 27 dalam Penyusunan Laporan Keuangan di Koperasi Karyawan Indosukma PT Indofood CBP Sukses Makmur Tbk - Novia Cynthia Maradesa; Jenny Angela Berdame (Global Leadership Organizational Research in Management, 2024)
This research aims to find out the financial reports in the Indosukma cooperative, so that the financial reports become relevant. Data was obtained by conducting interviews and documentation. The data analysis technique used is to describe research data and analyze financial reports at the Indo Sukma Employee Cooperative PT Indofood CBP Sukses Makmur. The research results show that in general the Indo Sukma Employee Cooperative PT Indofood CBP Sukses Makmur Tbk has implemented Statement of Financial Accounting Standards No. 27 in its financial reports. Based on the analysis and evaluation carried out, it turns out that PSAK No. 27 in Indosukma employee cooperatives has not been implemented properly, such as not presenting members' economic promotion reports, not presenting estimates of cooperative burdens.